KEPEMIMPINAN KEPALA SEKOLAH DALAM PEMBINAAN DI BIDANG KESISWAAN - Desmi Yanti (Manajer Pendididikan, 2020)
This qualitative study described how the leadership of the school principal on coaching students. The data were collected by observation, interview, and documentation. The results showed that the leadership of the school principal on coaching students is all ready well planned, even there are some lacks and needs improvement.